2012
DOI: 10.1038/nchembio.796
|View full text |Cite
|
Sign up to set email alerts
|

Structural basis of transfer between lipoproteins by cholesteryl ester transfer protein

Abstract: Human cholesteryl ester transfer protein (CETP) mediates the net transfer of cholesteryl ester mass from atheroprotective high-density lipoproteins to atherogenic low-density lipoproteins by an unknown mechanism. Delineating this mechanism would be an important step toward the rational design of new CETP inhibitors for treating cardiovascular diseases. Using EM, single-particle image processing and molecular dynamics simulation, we discovered that CETP bridges a ternary complex with its N-terminal β-barrel dom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

25
223
1
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 133 publications
(251 citation statements)
references
References 43 publications
25
223
1
2
Order By: Relevance
“…6 shows, the CETP tunnel significantly elongates from the crystal conformation and stabilized to an extended length of ϳ95 Å during the final 500-ns simulation time when CE N was linear. This finding is consistent with the recent EM structure of CETP bound to HDL and LDL, which suggested a more continuous hydrophobic tunnel, compared with the shorter 60-Å central cavity observed in the CETP crystal structure (21). We speculate that the constricted tunnel found in the CETP crystal structure is a consequence of the crystal packing effects, as was also observed in the crystal structures of other proteins (e.g.…”
Section: Conformational Flexibility Of Ce Is Assisted By Bending and supporting
confidence: 80%
See 2 more Smart Citations
“…6 shows, the CETP tunnel significantly elongates from the crystal conformation and stabilized to an extended length of ϳ95 Å during the final 500-ns simulation time when CE N was linear. This finding is consistent with the recent EM structure of CETP bound to HDL and LDL, which suggested a more continuous hydrophobic tunnel, compared with the shorter 60-Å central cavity observed in the CETP crystal structure (21). We speculate that the constricted tunnel found in the CETP crystal structure is a consequence of the crystal packing effects, as was also observed in the crystal structures of other proteins (e.g.…”
Section: Conformational Flexibility Of Ce Is Assisted By Bending and supporting
confidence: 80%
“…Interestingly, one of the CEs in the hydrophobic tunnel was in the bent conformation, whereas the second CE molecule was in the linear conformation. Recent cryopositive staining EM and optimized negative-staining electron microscopy (OpNS-EM) protocols combined with CETP C terminus-specific polyclonal antibody studies have suggested that CETP penetrates its C-terminal ␤-barrel domain into LDL or VLDL and its N-terminal ␤-barrel domain into HDL to form a ternary complex (21). Further, it was suggested that the aforementioned long continuous hydrophobic tunnel that traverses along the long axis of CETP can connect to the core of HDL and LDL simultaneously to facilitate the transfer of CEs and TGs between the lipoproteins.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Electron microscopy show virtually no CETP complexes bridging two HDLs, LDLs or VLDLs, implying CETP domain specificity for HDL (N-terminal) and LDL and VLDL (C-terminal) The co-existence of ternary complexes of HDL-CETP-LDL and HDL-CETP-VLDL and lipid transfer are consistent with the mechanistic model of cholesterol ester transfer through a tunnel within CETP, though at this point the continuous hydrophobic tunnel between the distal portions of the Nand C-terminal domains of CETP is hypothetical. Changes in hydrophobicity along the central cavity are suggested as one of the dynamic forces which favor a cholesteryl ester N-to C-terminus transfer [255]. Both CETP structure and circulating molar concentrations of lipoproteins are thought to contribute to CETPs physiological preference for HDL [256].…”
Section: Cholesteryl Ester Transfer Protein (Cetp) and Phospholipid Tmentioning
confidence: 99%
“…1 ) ( 12,18,19 ), and ii ) a tunnel mechanism in which CETP bridges two lipoproteins to form a ternary complex, with lipids fl owing from the donor to acceptor lipoprotein through the CETP molecule ( Fig. 2 ) (20)(21)(22). Proposed shuttle mechanism for cholesteryl ester transfer by CETP.…”
Section: Mechanism Of Action Of Cetpmentioning
confidence: 99%